and Compounds Affecting Interactions Between and Its Natural Enemies and - Wagner de Souza Tavares; Jesusa Crisostomo Legaspi; Ancidériton Antonio de Castro; Hany Ahmed Fouad; Muhammad Haseeb; Robert L. Meagher; Lambert H.B. Kanga; José Cola Zanuncio (SAGE Publishing, 2019)
The interaction Spodoptera exigua Hübner (Lepidoptera: Noctuidae) × its natural enemies Cotesia flavipes Cameron (Hymenoptera: Braconidae) and Podisus maculiventris Say (Heteroptera: Pentatomidae) × botanical compounds with and without synergist is unknown; therefore, it was studied under controlled conditions. The objective of this study was to evaluate the direct mortality of P. maculiventris nymphs and adults and indirect by this predator feeding on S. exigua larvae treated after being exposed to parasitism by C. flavipes . Brassica nigra L. (Brassicales: Brassicaceae) and Curcuma longa L. (Zingiberales: Zingiberaceae) compounds, with and without lead (II) oxide (PbO), were tested as insecticides. The mortality of first and second instars P. maculiventris was high with turmeric essential oil by topical application. The PbO increased the predator mortality in combination with turmeric powder, crude essential oil, and ar -turmerone. This last derivative caused also the highest mortality of P. maculiventris nymphs when ingested through treated S. exigua larvae that were previously subjected to parasitism. Turmeric powder and its derivatives, with and without PbO, should not be used in areas with P. maculiventris due to the high mortality caused to this predator.